Appreciation that inspires: The impact of leader trait gratitude on team innovation. (13th November 2021) - Li, Chenwei; Dong, Yuntao; Wu, Chia‐Huei; Brown, Michael E.; Sun, Li‐Yun
Summary: Although a leader's affective characteristics are believed to influence team processes and outcomes, the impact of leaders' discrete affective traits on team innovation remains unclear. This study addresses this issue by developing a multistage team‐level model that explains how team leaders' trait gratitude enhances team innovation. Specifically, we draw on the other‐praising perspective of gratitude to predict that leaders with trait gratitude tend to demonstrate humble behavior, which, in turn, promotes team voice and ultimately enhances team innovation. We also incorporate trait activation theory to theorize that leaders' perception of organizational support enhances the impact of trait gratitude on the leaders' humble behavior and its indirect effect on team innovation (via humble behavior and team voice). We found support for our research model using data of 71 teams collected from three sources in four phases. This study offers important insights into how and when leaders with high trait gratitude can foster team innovation and advances the existing gratitude research in the team context.